The Analysis of Quizizz as Formative Assessment Media in the Front Office Subject for Class XII AP 2 of SMK Singamandawa - Yasa, I Gede Santika; Wedayanthi, Luh Made Dwi; Suardana, I Putu Oka (Innovative: Journal Of Social Science Research, 2024)
This study aimed to analyze Quizizz as a formative assessment media for the Front Office subject for Class XII AP 2 at SMK Singamandawa. Based on observations, interviews, questionnaire distribution, and documentation of formative assessment results, Quizizz emerged as a very positive and successful assessment media. It facilitated student progress tracking, provided a fun learning experience, and aligned with learning objectives. Feedback from students and teachers highlighted the benefits of Quizizz in question quality, ease of use, efficiency, and effectiveness as a formative assessment media. Additionally, documentation of student formative assessment using Quizizz showed a good and consistent level of student achievement, even though there were challenges such as internet instability and browser compatibility. This study emphasized the suitability of Quizizz as a formative assessment media, especially for Front Office learning, and provided valuable insights for teachers who aimed to optimize formative assessment practices.